The Role of Urinary Aldosterone for the Diagnosis of Primary Aldosteronism - Ceral, J.; Malirova, E.; Ballon, M.; Solar, M. (Hormone and Metabolic Research, 2014)
When diagnosing primary aldosteronism, the measurement of urinary aldosterone after oral sodium loading is one of the currently recommended confirmatory tests. The aim of the study was to assess the repeatability and interpretation of urinary aldosterone in patients examined for suspected primary aldosteronism. Sixty-four hypertensive patients with suspected primary aldosteronism were prospectively enrolled and examined according to the study protocol. After antihypertensive medications interfering with renin-angiotensin-aldosterone system were withdrawn for at least 2 weeks, the confirmatory testing was performed: oral sodium loading preceded the collection of 24-h urine sample and subsequent saline infusion test. The identical procedures were repeated after 2 weeks. The concordant results of both saline infusion tests served for confirmation/exclusion of primary aldosteronism. Forty-nine patients were included in data analysis. Primary aldosteronism was excluded in 16, and confirmed in 33 individuals. The repeatability of urinary aldosterone was evaluated in 44 patients: the difference of urinary aldosterone levels ranged between 1 and 88% (median 31%). Ninety-three urine samples from 49 patients were used to validate the interpretation of urinary aldosterone in respect to the diagnosis of primary aldosteronism made by saline infusion testing; 96% sensitivity was characterized by urinary aldosterone ≥19 nmol/day, and 96% specificity was associated with urinary aldosterone ≥92 nmol/day. In 22 (45%) patients, urinary aldosterone remained in the “gray” zone between 19 and 92 nmol/day in all provided samples. The estimation of urinary aldosterone excretion after oral sodium loading is associated with marked intraindividual variability, and significant number of inconclusive results.
Keywords: primary aldosteronism; urinary aldosterone; secondary arterial hypertension